Identity Crisis in the Select Novels of Bharati Mukherjee: Exploring Identity Crisis and Feminist Perspectives in Bharati Mukherjee's Select Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper analyses issues of identity crisis in the select novels of Bharati Mukherjee. Novels of Bharati Mukherjee reflect its characters and their sensibilities with special reference to women characters. A closer look or observation of Bharati Mukherjee’s eight novels depicts that she has written all the novels with mainly feminist perspectives. In view of the fact that Bharathi Mukherjee’s female characters are the sufferer of immigration, all the critics focus her novels as constraints and consequences due to immigration but in fact the constraints are not because they are immigrants but because the women characters fight for their rights as a woman and then as a human being moreover for their identity in and abroad. Mukherjee has attempted to create a new association between male and female based on equality or impartiality, non-exploitation and no oppression so that the imaginative potentials of both are maximized as individuals and not as gender dichotomies. The woman is preparing now to be her own gravitational force, beyond the completeness of patriarchy. The man, as a representative of the patriarchal society has, at last, being jerked off the centre of woman’s gravitation.